The Contemporary Lithuanian Comic Culture and the History Motifs within it - Svitojus, Kasparas (Vilnius University Open Series, 2024)
The article focuses on comics published in Lithuania during the period of Lithuanian independence (1990–2022) and the historical plots used in them. The conducted research showed that the development of the comics format in Lithuania lags behind compared to other regions of the world. After researching Lithuanian comics, it became clear that most of them are historical. In Lithuania, historical comics can be divided into biographical, adventure, educational, or intended to convey a specific process, event or object. They are dominated by the 20th century events and personalities. In Lithuanian comics, history is presented through various phenomena such as clothing, architecture, recognizable historical figures, etc.
Keywords: comics culture; comics in Lithuania; Lithuanian comics; visual media; historical comics; historical motives